Pengaruh perlakuan blanching dan proporsi terhadap kualitas penyedap rasa alami dari jamur tiram dan jamur merang: The effect of blanching treatment and proportion on the quality of natural flavorings of oyster mushrooms and straw mushrooms - Azara, Rima; Budiandari, Rahmah Utami; Nurbaya, Syarifa Ramadhani; Adawiyah, Robiatul (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2024)
Straw mushrooms (Volvariella volvacea) and oyster mushrooms (Pleurotus ostreatus) contain natural glutamic acid which has the ability to provide a high-quality taste that is similar to the taste produced by Monosodium glutamate, making it suitable for use as a natural flavoring powder. This research uses RAK which is arranged factorially, namely the blanching method and the proportion of straw mushrooms (Volvariella volvacea) and oyster mushrooms (Pleurotus ostreatus). Based on the analysis of variance, it was found that there was an interaction between the blanching method and the proportion of straw and oyster mushrooms on physical analysis, namely yield, chemical analysis, namely water content and protein content and had no significant effect on organoleptic analysis. The best treatment results were the natural mushroom flavoring treatment with steamed blanching treatment and a mushroom proportion of 50%:50% (B1P2) which showed a yield of 3.69%, a lightness value of 74.31, a redness value of 5.74, a yellowness value of 14.30, water content 6.94%, protein content 41.36%, color organoleptic test 3.87 (like – really like), taste organoleptic test 3.20 (like) and aroma organoleptic test 3.20 (like). The aim of the research This is to determine the effect of the blanching method and the proportion of straw mushrooms (Volvariella volvacea) and oyster mushrooms (Pleurotus ostreatus) on the quality of the natural flavoring of mushrooms